Positional principle in practice of training to game on the keyboard of organno-piano type - Algin, Sergei (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Questions of perfection of technical skill of the musician attracted performers, teachers, academics at all times. This interminable problem of musical pedagogy represented by various schools of performance: L. S. Auer, R. N. Bazhilin, L. A. Barenbojm, O. A. Bloh, F. B. Buzoni, V. P. Vlasov, L. Godovsky, A. B. Goldenvejzer, I. Hoffmann, N. A. Davidov. M. Egorov, M. I. Imhanitsky, A. D. Korto, N. A. Kravtsov, Ф. R. Lips, F. List, V. H. Mazel, K. A. Martinsen, and. M. Mirek, M. Moshkovsky, G. G. Nejgauz, A. I. Poletaev, N. I. Rizol, V. A. Semyonov, S. E. Fejnberg, G. M. Tsypin, G. I. Shahov, F. F. Chopin, O. F. Shulpjakov, Ю. G. Jastrebov and many other. However, questions of technical training of musicians – performers by positional principle as basis of the organization of moves in musical performance are not enough developed in musical pedagogy. In the majority of the theoretical works, to some extent concerning questions of perfection of technical skill, this problem is not considered as system, in a complex. Till now there is no accurate definition, there is no unified valid term, which would be considered theoretically. All it leads to set of various approaches to studying this question and essentially reduces process of preparation of professional musicians – performers in the field of performance on musical instruments. So, this article is devoted for one of the main elements in development of performing technique on the keyboard of organ-piano type (a piano, an accordion, Kravtsov's free – bases keyboard) – for a positional principle. The concept and structure are considered of the given principle, and also are given some methodical recommendations about its realization. As the basic material for this article are used monographs, articles, the dissertational researches devoted to questions of development of the performing technique, considering various sides of positional principle of training have served. In article are used as general-theoretical methods (the analysis, generalization, ordering), and empirical (supervision). The basic conclusion of article is that the positional principle allows to add and concretize a number of the important questions in the theory and method of training on the organ-piano keyboard, concerning formations of method of performance of the musician and to approach more effectively to development of highly skilled experts in the field of performance by musical instruments, and also produce propitious conditions for technical development of mechanical skills of the musician and brings for it technique, discipline and organization.